1999
DOI: 10.1097/00005768-199902000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Rat liver lysosomal and mitochondrial activities are modified by anabolic-androgenic steroids

Abstract: The present data show that 8-wk ingestion of three different anabolic-androgenic steroids, either with or without concurrent exercise training, affects lysosomal hydrolases and mitochondrial respiratory chain electron transport in rat liver without modifying classical serum indicators of hepatic function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 33 publications
6
32
0
Order By: Relevance
“…These results suggest that BGLU levels could also be influenced by the male hormone. A similar conclusion was reached by Molano et al (24) in a study in which higher BGLU levels were observed in liver homogenates from androgenic steroid-treated rats than in liver homogenates from untreated animals.…”
Section: Discussionsupporting
confidence: 85%
“…These results suggest that BGLU levels could also be influenced by the male hormone. A similar conclusion was reached by Molano et al (24) in a study in which higher BGLU levels were observed in liver homogenates from androgenic steroid-treated rats than in liver homogenates from untreated animals.…”
Section: Discussionsupporting
confidence: 85%
“…This observation is consistent with previously reported results [7,21]. On the contrary, some studies reported that the supraphysiologic doses of AAS are associated with an increase in the plasma levels of these parameters [29][30][31].…”
Section: Alt (Iu/l) Ast (Iu/l) Alp (Iu/l)supporting
confidence: 93%
“…In addition, the conventional liver function tests do not always reflect liver abnormalities particularly at the initial stages. In this regard, previous studies indicate that prolonged AAS administration causes inflammatory or degenerative lesions in centrilobular hepatocytes, ultrastructural alterations in the canaliculi and degenerative changes in mitochondria and lysosomes without modifying classical serum indicators of hepatic function [6,7,21].…”
Section: Alt (Iu/l) Ast (Iu/l) Alp (Iu/l)mentioning
confidence: 96%
See 1 more Smart Citation
“…These results are also consistent with Welder et al (1995) who cited that AAS have toxic effects in primary rat hepatic cultures. Controversially, Molano et al (1999) reported that prolonged administration of anabolic steroid stanozolol had no significant effect on classical serum markers of liver function. The increment in serum AST and ALT activities may be attributed to the release of these enzymes from the cystol of liver cells into the blood circulation as a result of hepatocytes damage (Navarro et al, 1993).…”
Section: Discussionmentioning
confidence: 99%